Harmony with Nature: A Cultural Ecological Study of Mandailing Ethnic Philosophy on the Environment - Ahmad Muhajir (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2023)
This article aims to explore the profound philosophy of life held by the Mandailing ethnic group in maintaining the relationship between humans and the environment from a cultural ecological perspective. Employing an ethnohistorical approach, this research analyzes and synthesizes relevant ethnographic literature along with field research data. The focus of this study is on the philosophies